Crisp Bhutan Oyster Mushroom (Pleurotus pulmonarius): A Potential Innovative Product for Commercialization - Chuensumran, Ubol; Khunsee, Att (Journal of Food Health and Bioenvironmental Science, 2023)
This research was undertaken to create therapeutic mushroom products and disseminate knowledge to entrepreneurs. The researchers along with a community created product design and distribution channels and developed a brand for medicinal mushroom products based on the community's identity. Bhutanese oyster mushrooms were used to create mushroom products that consisted of Bhutanese oyster mushroom (88%), sugar (5%), vegetable oil (3%), soy sauce (2%), coriander seeds (1%) and salt (1%).The production method was conducted by to washing the mushrooms thoroughly, squeezing the water out and setting them aside; then mixing all ingredients together and dry in a hot air oven at 60°C for 90 min. Then the batter was fried in hot oil at 90-95°C for 5 min, and then placed in the oven at 150°C for 20 min to crisp and reduce the surface moisture of the product. The sensory preference (7.80 – 8.80 points) was at a high level. Moreover, the knowledge can be transferred to entrepreneurs to implement in real production. It is a product that has the potential to be marketed for distribution as a health food with an emphasis on semi-premium marketing which can be differentiated by demonstrating the value and nutrients of Bhutanese oyster mushrooms. This research included designing aesthetic, outstanding and unique packaging to create the identity for the community. Furthermore, a brand of medicinal mushroom products called “Hed Khik Khak or Giggling Mushrooms” was created. The feedback acceptance (99%) was at a high level. The product has been registered under the trademark for Klong Chik Sub-district Community Enterprise to be used with therapeutic mushroom products in the future.